1999
DOI: 10.1046/j.1432-1327.1999.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Human chemokine receptors CCR5, CCR3 and CCR2B share common polarity motif in the first extracellular loop with other human G‐protein coupled receptors

Abstract: Chemokine receptors (CRs) are 7-helix membrane proteins from the family of G-protein coupled receptors (GPCRs). A few human CRs act as cofactors for macrophage±tropic (M-tropic) human immunodeficiency virus type-1 (HIV-1) entry into cells, while others do not. In this study, we describe an application of molecular modeling techniques to delineate common molecular determinants that might be related to coreceptor activity, and the use of the data to identify other GPCRs as putative cofactors for M-tropic HIV-1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…CD4 is considered the primary receptor for HIV, where gp 120 and gp 41 (envelope proteins) mediate virus binding to the target cell membrane followed by consequent interaction with chemokine receptors CCR3 and 5 CCR2B or CXCR4 leading to merging of the host cell membrane and HIV membrane [63][64][65][66][67][68][69][70][71][72]. Other chemokines, CCR2, 3, 8 and 9, STRL33, Gpr15, Gpr1, APJ, ChemR23 and CX3CR1, are also used by HIV for host cell entry during in vitro infection [64,[73][74][75][76].…”
Section: Chemokine Receptors Acting As a Portal Of Entry For Human Im...mentioning
confidence: 99%
“…CD4 is considered the primary receptor for HIV, where gp 120 and gp 41 (envelope proteins) mediate virus binding to the target cell membrane followed by consequent interaction with chemokine receptors CCR3 and 5 CCR2B or CXCR4 leading to merging of the host cell membrane and HIV membrane [63][64][65][66][67][68][69][70][71][72]. Other chemokines, CCR2, 3, 8 and 9, STRL33, Gpr15, Gpr1, APJ, ChemR23 and CX3CR1, are also used by HIV for host cell entry during in vitro infection [64,[73][74][75][76].…”
Section: Chemokine Receptors Acting As a Portal Of Entry For Human Im...mentioning
confidence: 99%
“…Using CCR6-CCR5 chimeras in which the ECDs of CCR5 were substituted for CCR6 ECDs in various combinations, one group found that replacement of one or more ECDs prevents the efficient binding of CCR6 to its CCL20 ligand [25]. Because HIV uses selected ECDs of CCR5 to gain cell entry [26,27], it is possible that CCR6 may permit entry in a similar manner. It is likely not dependent solely on static molecular structures, but requires a complex and subtle conformation of multiple aspects of the three-dimensional receptor structure.…”
Section: Ccr6 As An Hiv Co-receptormentioning
confidence: 99%
“…Although several other chemokine receptors have been identified as potential entry factors [42][43][44][45][46], only CCR5 and CXCR4 appear to be important for infection by most clinical isolates of HIV-1 [47,48]. This observation is reflected in the current nomenclature for HIV-1 coreceptor use [49]; R5 for viruses that only use CCR5, X4 for viruses that only use CXCR4, and R5X4 for viruses that can use both receptors.…”
Section: Hiv-1 Coreceptor Usementioning
confidence: 99%